2018
DOI: 10.1186/s12886-018-0967-z
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-month results after the treatment of post-LASIK ectasia with allogenic lenticule addition and corneal cross-linking: a case report

Abstract: BackgroundTo report a first case of lenticule addition and corneal cross-linking for post-LASIK ectasia with associated corneal thinning.Case presentationLenticule addition followed by corneal cross-linking was performed on the left eye of a patient with post-LASIK ectasia. Postoperatively, the corneal power and elevation were stable with a remarkable improvement in corneal thickness, and the lenticule had merged with the adjacent corneal stroma at 30 months follow-up. The patient’s corrected distance visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Corneal power and astigmatism did increase after lenticular implantation, but the authors hypothesize that this was due to the refractive error of the implanted lenticule (−2.75 DC, DC = diopters cylinder). This study was significant because it demonstrated 5 years of stability of the implanted lenticule, with no evidence of immunogenic rejection or regression of visual acuity in a patient with post-LASIK ectasia [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Corneal power and astigmatism did increase after lenticular implantation, but the authors hypothesize that this was due to the refractive error of the implanted lenticule (−2.75 DC, DC = diopters cylinder). This study was significant because it demonstrated 5 years of stability of the implanted lenticule, with no evidence of immunogenic rejection or regression of visual acuity in a patient with post-LASIK ectasia [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study ( Li et al, 2018 ), lenticule addition followed by ATE-CXL was performed on a patient with post-LASIK ectasia. Improved CDVA and stable corneal keratometry and elevation was observed at 30 months postoperatively; thus, lenticule addition prior to ATE-CXL was proven to be a potential treatment option for patients with keratectasia associated with a thin cornea.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend investigating recellularized customized SMILEextracted lenticules (which combine the benefits of planar and negative meniscus-shaped lenticules) with mesenchymal stem cells in a large number of advanced keratoconus patients, as multiple studies have shown the feasibility of regenerating the corneal stroma using autologous adipose-derived adult stem cells [57,69,71] . Table 2 [49,[53][54][55][56][60][61]65,67,74] summarizes clinical studies investigating SMILE-extracted lenticule applications in corneal ectasia treatment. Patch Graft for Glaucoma Tube Implants Wang et al [41] compared the efficacy of SMILE-extracted lenticules and the sclera as patch graft to prevent glaucoma drainage tube exposure.…”
Section: Smile-extracted Lenticules In Ophthalmologymentioning
confidence: 99%
“…Since then, various animal models have shown the effectiveness and safety [53] Case series Post-LASIK ectasia 3 13 Safe surgical approach for the treatment of post-LASIK ectasia, especially for severe cases with cornea thickness less than 400 μm. Li et al (2018) [54,74]…”
Section: Corneal Tissue Engineering and Animal Studiesmentioning
confidence: 99%